2021
DOI: 10.7554/elife.68549
|View full text |Cite
|
Sign up to set email alerts
|

Cortex cis-regulatory switches establish scale colour identity and pattern diversity in Heliconius

Abstract: In Heliconius butterflies, wing colour pattern diversity and scale types are controlled by a few genes of large effect that regulate colour pattern switches between morphs and species across a large mimetic radiation. One of these genes, cortex, has been repeatedly associated with colour pattern evolution in butterflies. Here we carried out CRISPR knockouts in multiple Heliconius species and show that cortex is a major determinant of scale cell identity. Chromatin accessibility profiling and introgression scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 87 publications
(162 reference statements)
3
69
0
Order By: Relevance
“…transcription factors optix (Reed et al, 2011) and aristaless (Westerman et al, 2018), signalling ligand WntA (Martin et al, 2012;Mazo-Vargas et al, 2017) and cycle-cell regulator cortex (Nadeau et al, 2016;Saenko et al, 2019). Thus, the establishment of the colour patterns takes place through a specific kinetic of these genes during metamorphosis and wing formation (Connahs et al, 2016;Hines et al, 2012;Livraghi et al, 2021).…”
Section: Indeed Offspring Of Crosses Between Individuals Of Different...mentioning
confidence: 99%
See 1 more Smart Citation
“…transcription factors optix (Reed et al, 2011) and aristaless (Westerman et al, 2018), signalling ligand WntA (Martin et al, 2012;Mazo-Vargas et al, 2017) and cycle-cell regulator cortex (Nadeau et al, 2016;Saenko et al, 2019). Thus, the establishment of the colour patterns takes place through a specific kinetic of these genes during metamorphosis and wing formation (Connahs et al, 2016;Hines et al, 2012;Livraghi et al, 2021).…”
Section: Indeed Offspring Of Crosses Between Individuals Of Different...mentioning
confidence: 99%
“…To this end, we sequenced RNA from multiple tissues and developmental stages to generate a reference transcriptome for M. marsaeus -the first to date for an ithomiine species -as a tool to investigate gene expression in the two subspecies phasiana and rileyi. We focussed on two stages of pupal wing discs, where colour patterns form in butterflies (Connahs et al, 2016;Hines et al, 2012;Livraghi et al, 2021), and in adult female antennae, where chemical signals are detected, to screen for differentially expressed genes between subspecies and throughout development. We also undertook a candidate gene approach and looked more specifically at the expression of genes known to be involved in colour pattern variation and in chemosensory activity in other Lepidoptera.…”
Section: Significancementioning
confidence: 99%
“…In recent years, reverse genetics research has revealed a surprising connection between the molecular machinery underlying the development of pigmented wing patterns and the ultrastructure of butterfly scales in various species (Zhang, Mazo-Vargas and Reed, 2017; Concha et al ., 2019; Fenner et al ., 2020; Livraghi et al ., 2021). However, our QTL are not associated with any known colour pattern gene of large or small effect in Heliconius ( aristaless, WntA, vvl, cortex and optix - located on chromosomes 1, 10, 13, 15 and 18 respectively) (Nadeau, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Most changes have been mapped to just four major effect pigment patterning genes: optix, cortex, aristaless1, and WntA (Figure 3B) [40,[46][47][48][49][50][51]. Responsible for establishing wing scale cell identity and competence to respond to TFs more directly involved in pigmentation [reviewed by 51]), cortex and WntA act at a higher tier in the GRN (Figure 3B, top): cortex is necessary to specify "Type II/III" scales [52]; and optix is responsible for further differentiation into Type III scales and promotion of red ommochrome production, while repressing the melanin pathway [53] (Figure 3B, middle right). In the absence of cortex, cells take on the "Type I" fate in which aristaless1 dictates white or yellow pigmentation via repression of yellow ommochrome production [54] (Figure 3B, middle left).…”
Section: Evolution Of the Heliconius Pigmentation Grnmentioning
confidence: 99%